EXAMINING THE IMPACT OF ARTIFICIAL INTELLIGENCE ON AUTOMATION AND EFFICIENCY IN MANUFACTURING SYSTEMS - Ruli Fahmi, Mohamad (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background: The integration of Artificial Intelligence (AI) in manufacturing systems has revolutionized the way industries operate, offering significant improvements in automation, efficiency, and quality control. As manufacturing processes become increasingly complex, AI technologies such as machine learning, robotics, and computer vision have enabled manufacturers to streamline operations, reduce costs, and enhance productivity. Aims: The primary aim of this research is to examine the role of AI in enhancing operational efficiency and productivity within manufacturing environments. Specifically, the study seeks to evaluate the impact of AI on key areas such as predictive maintenance, robotics in production, quality control systems, and supply chain management. Additionally, it aims to assess the implications of AI on workforce dynamics and identify the benefits and challenges manufacturers face when implementing AI technologies. By doing so, the research intends to provide valuable insights into how AI adoption can drive sustainable growth and competitiveness in the manufacturing sector. Research Method: This study employs a mixed-methods approach, combining both qualitative and quantitative research methods to gain a comprehensive understanding of AI's impact on manufacturing. The qualitative component involves in-depth interviews with industry professionals, AI experts, and managers in manufacturing companies that have adopted AI technologies. The quantitative aspect consists of surveys distributed to manufacturing professionals to gather data on AI applications and their effectiveness. Results and Conclusion: The results of the study demonstrate that AI significantly enhances operational efficiency across various dimensions of manufacturing systems. Key benefits include reduced downtime through predictive maintenance, improved production speed and accuracy with robotics, enhanced product quality through AI-powered quality control systems, and optimized supply chain management. The integration of AI has also transformed the workforce, requiring reskilling and upskilling of employees. Despite challenges such as high initial costs, data integration issues, and concerns about workforce displacement, the study concludes that the long-term advantages of AI adoption outweigh these obstacles. Manufacturers that embrace AI technologies gain a competitive edge in the market by improving productivity, reducing operational costs, and enhancing the flexibility of their operations. Contribution: This research contributes to the existing body of knowledge by providing a detailed analysis of AI's role in modern manufacturing systems. The study not only highlights the technical and operational advantages of AI but also addresses the social implications, particularly in terms of workforce adaptation and skill development. By examining case studies and gathering insights from industry professionals, the research offers practical recommendations for manufacturers considering AI adoption. The findings can guide decision-makers in optimizing AI integration, ensuring that they realize both immediate and long-term benefits while mitigating potential challenges.